Association between resilience and posttraumatic stress disorder among Brazilian victims of urban violence: a cross-sectional case-control study - Teche,Stefania Pigatto (2017)
Abstract Introduction This study investigated the association between resilience and posttraumatic stress disorder (PTSD) among Brazilian victims of urban violence. It also compared defense mechanisms, parental bonding, and childhood trauma between those who developed PTSD and those who did not. Methods This cross-sectional case-control study included 66 adult subjects exposed to recent urban violence in southern Brazil – 33 with PTSD and 33 healthy controls matched by sex and age – who were administered the Resilience Scale, Defense Style Questionnaire, Parental Bonding Instrument, and Childhood Trauma Questionnaire. The statistical tests used were the McNemar test for categorical variables, the Wilcoxon signed-rank test for continuous asymmetric variables, and the paired Student t-test for continuous symmetric variables. Results The PTSD group showed lower total Resilience Scale scores compared with controls (128.4±20.7 vs. 145.8±13.1, respectively; p = 0.01), along with a lower ability to solve situations and lower personal values that give meaning to life (p = 0.019). They also had lower rates of mature defense mechanisms (p < 0.001) and higher rates of emotional (p = 0.001) and physical (p = 0.003) abuse during childhood. Conclusion Lower levels of resilience, especially the ability to solve situations and having personal values that give meaning to life, immature defense mechanisms, and emotional and physical abuse in childhood are associated with PTSD in adult Brazilian victims of urban violence.